Knowledge of sexual abuse and resistance ability among children with intellectual disability. (February 2023) - Jojo, N.; Nattala, P.; Seshadri, S.; Krishnakumar, P.; Thomas, S.
Abstract: Background: Sexual abuse is a global concern among children with intellectual disabilities. Sexual abuse is frequent and long-lasting when the victim is a child with an intellectual disability. Moreover, the rate of sexual abuse is two to eight times the rate in the general population. Objective: This study aimed to investigate the knowledge of sexual abuse and resistance ability among children with intellectual disabilities. Participants and setting: The study was conducted among 120 children with mild or moderate intellectual disabilities attending twelve schools for specific purposes. Methods: We adopted a cross-sectional design to assess knowledge and resistance ability. Personal Safety Questionnaire and Modified What If Situation Test were administered verbally during individual interviews. Institutional Ethics Committee approved our study. Results: Current study suggests that children with intellectual disabilities have average knowledge ( M = 6.6, SD = 1.6) regarding sexual abuse. More than 90 % of children demonstrated poor reporting skills. Although children exhibited good knowledge in differentiating appropriate from inappropriate touch requests, most children reported they would not disclose this incident to anyone. Conclusions: This study strongly suggests the need for a structured training program for children with intellectual disabilities to prevent sexual abuse.